PEMETAAN PERSEBARAN PENYAKIT BUNCHY TOP PADA TANAMAN PISANG DI PROVINSI LAMPUNG - Joko Prasetyo dan Sudiono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2004)
Distribution mapping of bunchy top of banana in Lampung Province. Studies on the occurrence of banana bunchy top were conducted in Lampung province from March to May 2003. This study were aimed to make distribution map of banana bunchy top in Lampung. The stratified random sampling were used. The sample comprised 6 districts out of 10 districts in Lampung. Three subdistrics were randomly selected in each district and then 3 villages were also selected in each subdistrict. In each village 3 famer”s gardens were selected as observation area. The distribution map shows that banana bunchy top has spread throughout the 6 districts visually observed, but only 4 districts, that bunchy top incidence could be examined. Banana bunchy top incidence in Bandar Lampung, South Lampung, Central Lampung, and North Lampung were 2.31, 2.23, 1.06, and 0.84 % respectively. Bunchy top virus attacked various types, among them are janten (55.23%), muli (38.88%), kepok (30.47%), ambon (21.52%), raja sere (19.76%), nangka 4.64%), and lilin (3.84%). There were no disease incidence on cultivar tanduk, rejang and susu, thus this fact might be indicated resistance phenomena of these cultivars.